Managing stress from the perspectives of al-Ghazali andal-Dihlawi / Nur Syazana Adam ... [et al.] - Adam, Nur Syazana; Junoh, Noraini; Yusoff, Zulkarnain; Syed Omar, Syed Hadzrullathfi; Mohamad, Abdul Manam; Mat Zin, Mohd Nazri (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
Stress generally refers to a mental and spiritual state that is unable to accept a situation to cause emotional stress. This condition will be even worse if the individual does not seek treatment or therapy to prevent this emotional instability from lasting. As such, this study aims to analyze methods in dealing with stress based on Islamic perspectives in particular according to the views of al-Ghazali and al-Dihlawi. This qualitative study used data collection methods in the form of content analysis. The data was analyzed based on inductive, deductive, and comparative methods to obtain the results of the study. The study found that the devotion in prayer highlighted by al-Ghazali and al-Dihlawi can facilitate stress management. This is because of the steadfastness of one's heart towards the Creator and the peace of one's soul when feeling devout in prayer. Consequently, people who are devout in prayer are indeed able to face challenges while reducing stress in life